2013
DOI: 10.1002/adfm.201203386
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Transformation of Fullerenes

Abstract: Experimental fi ndings and associated theoretical insights regarding the photochemical transformation of fullerenes are reported, which challenge the conventional wisdom in the fi eld and point out a viable path towards improved fullerene-based electronic devices. It is shown that the effi ciency of the photochemical monomer-to-dimer transformation of the fullerene [6,6 ′ ]-phenyl-C 61 -butyric acid methyl ester (PCBM) is strongly dependent on the light intensity, and this is utilized to demonstrate that direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 41 publications
1
40
0
2
Order By: Relevance
“…A possible explanation for this synergy is that fullerene oligomerization reactions are strongly concentration-dependent and not directly proportional to light intensity due to a partial of back-reaction from excited triplet states. 45 An enhancement of WBC device stability after light treatment could indicate a higher PC 60 BM concentration available for oligomerization thereby restricting the degradation of performance. However, UV-vis data ( Figure S2) confirm that the average PCDTBT and PC 60 BM composition remains similar regardless of solution casting technique.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for this synergy is that fullerene oligomerization reactions are strongly concentration-dependent and not directly proportional to light intensity due to a partial of back-reaction from excited triplet states. 45 An enhancement of WBC device stability after light treatment could indicate a higher PC 60 BM concentration available for oligomerization thereby restricting the degradation of performance. However, UV-vis data ( Figure S2) confirm that the average PCDTBT and PC 60 BM composition remains similar regardless of solution casting technique.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that light exposure of C 60 and PC 60 BM films can result in fullerene oligomerization, thereby substantially reducing their solubility 18,26 . Such fullerene oligomerization is therefore the most probable origin of the enhanced morphological stability of PCDTBT:PC 60 BM blend films following light exposure reported above.…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45] The Nyquist plots weremeasured under 1sun illuminationwith an applied bias voltage of 0.8 Vint he frequency range from 2MHz to 0.5 Hz. [39,47] In the presentc ase, the device without t-BAI doping exhibits as lope of 1.87 kT/q, [48,49] indicating as trong energy loss owing to trap-assisted recombination. In the plots, the low-frequency one relatest ot he recombination resistance (R rec )a tt he interface of the perovskite/charget ransport layer (CTL), the high-frequency one concerns the charge-transfer resistance( R ct )f rom perovskite to CTL, and R s is the sheet resistance of the conductive electrode.…”
Section: Resultsmentioning
confidence: 57%